1995
DOI: 10.1046/j.1471-4159.1995.64052273.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Adrenergic and Peptide Stimulation in the Rat Pineal: Pituitary Adenylate Cyclase‐Activating Peptide

Abstract: The 27 amino acid peptide, pituitary adenylate cyclase‐activating polypeptide (PACAP‐27), and its 38 amino acid analogue, PACAP‐38, stimulate serotonin‐N‐acetyltransferase (NAT) activity and N‐acetylserotonin (NAS) and melatonin content of pineal glands from adult rats. Maximal stimulation of rat pineal NAT by PACAP‐38 is not increased further significantly by concurrent stimulation with the two related peptides, vasoactive intestinal polypeptide (VIP) and/or peptide N‐terminal histidine C‐terminal isoleucine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Exposure of pinealocytes to graded concentrations of PACAP enhances cAMP production (Rekasi and Czompoly, 2002) and causes an increase in the activity of two key enzymes of the melatonin biosynthetic pathway, serotonin-N-acetyltransferase (Yuwiler et al, 1995;Schomerus et al, 2002) and hydroxyindole-O-methyltransferase (Ribelayga et al, 1997). Consistent with these observations, PACAP has been found to stimulate melatonin secretion by perifused rat pineal glands (Simonneaux et al, 1993) and cultured pinealocytes (Chik and Ho, 1995;Simonneaux et al, 1998;Schomerus et al, 2002).…”
Section: Actions Of Pituitary Adenylate Cyclase-activating Polypeptidmentioning
confidence: 60%
“…Exposure of pinealocytes to graded concentrations of PACAP enhances cAMP production (Rekasi and Czompoly, 2002) and causes an increase in the activity of two key enzymes of the melatonin biosynthetic pathway, serotonin-N-acetyltransferase (Yuwiler et al, 1995;Schomerus et al, 2002) and hydroxyindole-O-methyltransferase (Ribelayga et al, 1997). Consistent with these observations, PACAP has been found to stimulate melatonin secretion by perifused rat pineal glands (Simonneaux et al, 1993) and cultured pinealocytes (Chik and Ho, 1995;Simonneaux et al, 1998;Schomerus et al, 2002).…”
Section: Actions Of Pituitary Adenylate Cyclase-activating Polypeptidmentioning
confidence: 60%
“…Functional studies have demonstrated that VIP also stimulates adenylate cyclase activity (Kaneko et al 1980a), cAMP production (Kaneko et al 1980b, Chik et al 1988, Rekasi et al 1998, CREB phosphorylation (Schomerus et al 1996), AA-NAT activity (Kaneko et al 1980a, Yuwiler 1983) and MT secretion (Simonneaux et al 1990, Rekasi et al 1994 with, however, much less potency than NE. PACAP also stimulates cAMPinduced AA-NAT activity and MT secretion (Simonneaux et al 1993, Chik & Ho 1995, Yuwiler et al 1995 in rat pineal gland in a similar manner to VIP.…”
Section: Introductionmentioning
confidence: 83%
“…In addition to the adrenergic regulation of MT secretion, an increasing number of peptidergic neurons have been reported to play a modulating role in pineal function (Simonneaux 1995, Yuwiler et al 1995, Moller et al 1996, Rekasi et al 1998, Pfeffer et al 1999. Among the peptides of the secretin superfamily, VIP and PACAP proved to be the most potent in stimulating MT synthesis and release (Simonneaux et al 1990, 1993, Rekasi et al 1994, Pfeffer et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations